Sources of economically valuable traits for covered oat breeding - I. I. Rusakova; G. A. Batalova; Ju. E. Vedernikov; M. V. Tulyakova (Аграрная наука Евро-Северо-Востока, 2016)
Using of genetic diversity is one of the factors of successful oat breeding. Screening of sources with high yield, resistance to abiotic (high soil acidity and drougth) and biotic (pathogens) stressors, early maturity, high grain quality is actual for Volga-Vyatka region. Studies were conducted in contrast climatic conditions on favorable and natural acid (provocative) soil backgrounds in Kirov region. The most promising accessions are 15068 Konkur (Russia) and 14983 Hybrid (Mexico) having resistance to soil acidity and drought and high grain quality. Accessions 15069 Rysak (Russia), 14967 Florida 657 (USA), and 15082 Ivory (Germany) are recommended to include in crossing with adaptive varieties of local breeding. Sources are selected having high resistanse to soil acidity and high grain quality: 15065 Irtysh (Russia), Yakov (Russia), 15127 SW Betania (Sweden), 15052 Rigja (Norway), 14966 Winter Dum (South Africa) etc. For breeding to early maturity accessions 22h10 Eaton (Russia), 14964 Zwarte president (Netherlands), 15257 RA 7836-416, 15258 RA 7836-2701, 15264 RA 7967-11690, 14620 Newman (USA), 15111 L-15 (Colombia), 15027 C.I. 9101 (Turkey), 14991 ОА 309 (Canada) etc are recommended as paternal forms. Sources of high grain quality and resistance to pathogens are 15184 AC-7 (Russia), 14970 Illinois 62-1532 (USA), 14535 Urano Inia (Chile) etc.